The workers with Disabilities’ Access to Workplace Inclusion in Postmodern Model Perspective - Argyo Demartoto (Universitas Gadjah Mada, 2018)
People with disabilities are often labeled negatively and treated discriminatively within community, including in workplace, so that only a few of them are absorbed in either formal or informal job. Meanwhile, they are entitled to get productive and reasonable job in order to realize their aspiration, to improve their life condition, and to participate actively within community. This article studies the workers with disabilities’ access to workplace inclusion in Postmodern Model Perspective in Surakarta. Accidental sampling was used to select informant; data collection was carried out through observation, in-depth interview, and document. Data validation was carried out using method and data source triangulations. The result of research showed that the access of the workers with disabilities to workplace inclusion has not been optimal yet, because the opportunity was still more limited compared with that for their non-disabled counterparts. Although inclusive work environment has diverse potential human resources and the workers with disabilities’ perspective, creativity, innovation, and problem solving ability have not been utilized maximally. In the construction process, workers with disabilities should actively participate in planning, implementation, and monitoring and evaluation so that the guarantee of workers with disabilities’ accessibility to building, transportation and communication media, workplace inclusion and many facilities can be met. The improvement of accessibility in the term of independency, rehabilitation, and social grant, and the maintenance of social wellbeing level and equal right to grow and to develop people with disabilities’ talent, ability, and social life are important to develop workplace inclusion. Prioritizing and respecting pluralism, equity, dignity, and active public participation simultaneously and sustainably will lead to the realization of inclusive society.